A Legal analysis on Occupational health of Mining workers from Indian Labour perspectives - MANO, Mrs. S. (South Eastern European Journal of Public Health, 2024)
The mining sector in India is a significant contributor to the economy but presents severe occupational health hazards for workers. This study provides a legal analysis of the occupational health standards for mining workers from the Indian labor law perspective. It examines various legislative frameworks, judicial interventions, and policy initiatives addressing workplace safety, health risks, and compensation mechanisms for mining laborers. Through an extensive review of laws such as the Mines Act, 1952, and Factories Act, 1948, the study highlights gaps in implementation and explores recommendations to strengthen labor protections in the mining industry.